A Natural Dietary Flavone Myricetin as an α-Hemolysin Inhibitor for Controlling Staphylococcus aureus Infection - Wang, Tingting; Zhang, Peng; Lv, Hongfa; Deng, Xuming; Wang, Jianfeng (Frontiers in Cellular and Infection Microbiology, 2020)
Staphylococcus aureus, an important agent for lethal bacterial infections, can cause a broad spectrum of diseases in various host species. The emergence of multidrug-resistant and highly virulent strains has raised increasing concerns about the novel therapeutic strategies or agents available for treating S. aureus infection. The critical role of Hla, an essential virulence determinant, in the pathogenicity of S. aureus renders this toxin an attractive target for effective therapeutic applications. Here, we have identified myricetin as an effective inhibitor of Hla that simultaneously inhibits Hla production and neutralizes Hla activity without affecting bacterial growth. Myricetin treatment reduced the oligomerization of Hla and Hla-mediated biofilm formation. The addition of myricetin to the coinfection system of host cells and S. aureus significantly decreased cell injury and downregulated the inflammatory response in cells. Furthermore, S. aureus-infected mice that received myricetin showed alleviated tissue damage in the lung. Our results indicated that myricetin inhibits S. aureus virulence by targeting Hla and downregulates the inflammatory response in host cells. Overall, in addition to traditional antibiotics with antibacterial activity, myricetin may represent a potential candidate and strategy for S. aureus infection.